In 2012 the superintendencia de industria y comercio entity with social responsability (2013)
In the Superintendencia de Industria y Comercio seeks to add value to its mission and contribute to sustainable development through the development of responsible socially practices. Accordingly, it has hosted the Guide ISO 26000 Social Responsibility with a compromise to advance its implementation. For this is to each actions within the principles of good governance, quality and transparency to ensure good performance of the public service in the Superintendencia de Industria y Comercio and the, building trust among consumers and entrepreneurs and all our stakeholders.